Funfax stickers : trucks - Pritchard, Louise (FUNFAX New York, 1999)
This interactive sticker book captivates young truck enthusiasts with its colorful illustrations and a variety of stickers. It encourages children to explore different types of trucks while developing their fine motor skills and creativity.